Socio-demographic Characteristics of Unmet Need for Family Planning in Maluku, 2015 - Pahlawaniati, E; Prasetyo, S B (KnE Life Sciences, 2019)
Unmet need for family planning services is the proportion of women of childbearing age who do not want children any more or want to delay childbirth but do not use contraception to prevent pregnancy. In 2012, Maluku was one of the provinces in Indonesia with high unmet need compared to other regions. This study aimed to explore/examine the relationship between unmet need and socio-demographic characteristics. The data take from secondary data of National Socio-Economic Survey (Susenas) in 2015. The number of samples used in the analysis was 3.276 married women of reproductive age. The results showed that of all married women of childbearing age, 30.71% were women with unmet need and the highest level of unmet need was in the district of Southeast West Maluku. Then, 2.422 women who need family planning services divided into groups of met demand and unsatisfied need groups. Multivariable binary logistic regression showed that age group, the age at first marriage, the number of living children, child mortality experience and region simultaneously associated with the status of unmet need for family planning. However, education and work status were not related to the unmet need for family planning significantly. The dominant factor associated with unmet need status for family planning in women were the age at first marriage and region. Most of the reason respondents who did not use contraception were due to adverse side effects on unmet need for spacing and other ideas on the unmet need for limiting. Keywords: socio-demographic, unmet need, women, Maluku.